SUN-602 A Case of Primary Squamous Cell Carcinoma of the Thyroid Gland - Vekaria, Shivani (J Endocr Soc, 2019)
Introduction: Primary squamous cell carcinoma (SCC) of the thyroid gland is an extremely rare thyroid malignancy. Currently, there is no consensus in management of this malignancy. We present a case of an invasive SCC of the thyroid gland. Clinical Case: A 70-year-old woman with a history of type 2 diabetes mellitus, hypothyroidism, and hypertension presented with shortness of breath, cough, and dysphagia for one-month duration. She recently was found to have bilateral thyroid nodules on thyroid ultrasound: a 2.8-cm left mid-gland nodule and a 2.4-cm right mid-gland peripherally calcified nodule. Computed tomography scan of the neck and soft tissue showed that the thyroid was markedly enlarged and contained calcified nodules, the largest measuring 2.3 cm. The enlarged thyroid displaced the subglottic airway and trachea leftward, and the esophagus was encased by this tumor. She underwent ultrasound-guided fine needle aspiration biopsy for both right and left thyroid nodules. Pathology of the biopsy revealed well-differentiated, keratinizing SCC. Given that primary squamous cell carcinoma of the thyroid is rare, the decision was made to pursuit direct laryngoscopy, bronchoscopy, esophagoscopy with biopsy to confirm diagnosis, which revealed intratracheal invasion of the tumor. Pathology of the biopsy confirmed invasive SCC. Due to intratracheal invasion of the tumor, patient was recommended to start chemotherapy and radiation instead of surgical resection with tracheostomy. Conclusion: Squamous cell carcinoma of the thyroid gland is a rare thyroid malignancy that carries a poor prognosis. This disease is seen predominantly in females with the mean age of diagnosis in the sixth decade. The presenting signs and symptoms are often an anterior neck mass or compressive symptoms such as dysphagia, dyspnea, or hoarseness. Once pathology confirms the diagnosis of squamous cell carcinoma, one must evaluate whether the malignancy is a primary thyroid malignancy or a secondary malignancy, either by direct extension of a head and neck cancer or metastasis. For treatment, surgical resection with adjuvant chemotherapy and radiation is usually recommended, though there is no consensus about treatment modality given its rarity. In the case of our patient, surgical removal could be not done as the malignancy had invaded the trachea and vocal cord, making a tracheostomy unfeasible. As a result, our patient started treatment with chemotherapy and radiation and will be reassessed for surgical resection at a later time. References: Cho JK, Woo SH, Park J, Kim MJ, Jeong HS. Primary squamous cell carcinomas in the thyroid gland: an individual participant data meta-analysis. Cancer Med. 2014;3(5):1396-403.